From Theory to Practice: Systematic Literature Insights on Work Motivation via Transformational Leadership and Culture - Banjarnahor, Astri Rumondang; Juliater Simarmata; Esti Liana; Sarinah Sihombing (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2025)
This study explores the influence of transformational leadership and organizational culture on employee work motivation through a systematic literature review using the PRISMA approach. It analyzes 61 articles from Scopus-indexed journals (2014–2024) to identify the synergy between transformational leadership and organizational culture in enhancing both intrinsic and extrinsic employee motivation. Transformational leadership has been shown to be effective in creating a clear vision, empowering employees, and fostering emotional engagement. In contrast, a strong organizational culture reinforces accountability, collaboration, and the recognition of individual contributions. This research addresses a gap in understanding how leadership styles interact with organizational culture to drive employee motivation. It provides a structured synthesis of leadership strategies that enhance motivation, highlighting the significance of intrinsic motivation in fostering innovation and long-term sustainability, while recognizing that extrinsic motivation remains essential for short-term performance improvement. The findings emphasize the importance of cultural variations in implementing organizational values, as national contexts influence the effectiveness of leadership. This study offers theoretical contributions by integrating perspectives from leadership, motivation, and organizational culture research, while also providing practical insights for managers to align leadership strategies with cultural values. The PRISMA methodology ensures a rigorous selection of sources, with inclusion criteria focused on Scopus-indexed peer-reviewed articles published between 2014 and 2024.